THE FACTORS AFFECTING LOCAL GOVERNMENT FINANCIAL STATEMENT QUALITY AT SKPD BANDUNG - Dini Wahjoe Hapsari, Dudi Pratomo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Based on PP. 71 of 2010, central and local government reports must be reliable, relevant, comparable and understandable. The quality of government financial reports is strongly influenced by the competence of human resources and the regional financial accounting system. The competence of human resources is measured by knowledge, skill and attitude. The regional financial accounting system is measured by the implementation of SAP and government financial statement procedures. Data collection was done by giving a questionnaire to all SKPD located in Bandung City Government. Based on respondent questionnaires, all data are tested for validity and reliability. If all data were valid and reliable, we continued to the classical assumption test. Finally, we calculated F-tests, t-tests and multiple linear regression. The test results show that the competence of human resources does not affect the quality of financial statements. This is due to one indicator of knowledge that shows the lack of human resources regarding knowledge. Regional Financial Accounting System does not affect the financial statements can be seen from not well-implemented procedures in the Regional Financial Accounting System.